Infrastructure Management to Support Logistic Distribution and Accessibility of Deltamas Industrial Estate - Anisa Mahadita Candrarahayu; Efendhi Prih Raharjo; Anggun Prima Gilang Rupaka (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2023)
Infrastructure management is a development from strategic management which is part of sustainable economic development. This study aims to determine the characteristics of movement, traffic performance on toll roads and main roads, cost savings associated with industrial activities in West Cikarang to West Karawang region to improve the logistic distribution and accessibility of the Deltamas Industrial Estate Area. The visum program was developed as effort to analyzed transportation network in the study area referring to survey results obtained. The results stated that every road network development there was an increase in speed and decrease in v/c ratio so as to improve network performance. In addition, the results of study also concluded that there were savings in the analysis of economic costs related to travel costs and experienced reduction in air pollution levels which can be improved logistic distribution. For this reason, strengthening network performance in encouraging increased accessibility is needed.